THE INFLUENCE OF WORK-LIFE BALANCE AND WORKLOAD ON JOB SATISFACTION OF HEALTHCARE WORKERS - Ari Tri Utami; Kosasih (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of work-life balance and workload on job satisfaction among healthcare workers in a hospital (Hospital X). The research uses a quantitative approach with a cross-sectional design. The sample consists of 100 healthcare workers selected using purposive sampling. Data were collected through a structured questionnaire measured using a Likert scale. The data analysis technique employed multiple linear regression analysis, preceded by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The results of the study indicate that all research instruments are valid and reliable. Furthermore, the findings show that work-life balance has a positive and significant effect on job satisfaction, while workload has a negative and significant effect on job satisfaction. Simultaneously, work-life balance and workload significantly influence job satisfaction. The coefficient of determination (R²) shows that 46.4% of job satisfaction can be explained by the independent variables, while the remaining 53.6% is influenced by other factors not examined in this study. In conclusion, improving work-life balance and managing workload effectively are essential strategies to enhance job satisfaction among healthcare workers, which ultimately contributes to better healthcare service quality.